The prospects of extraction of collagenolytic enzymes from hydrobionts of Antarctic region - N.G. Raksha; D.V. Gladun; O.M. Savchuk; L.I. Ostapchenko (Ukrainian Antarctic Journal, 2015)
Marine organisms have been recognized as rich sources of bioactive compounds with valuabe biotechnology potential. Enzymes extracted from marine hydrobionts have gained much attention because of their unique  quite specific properties that determined their profound applications in chemical, medical, food industries and molecular biology experiments. In this regard, our work focused оn investigation of proteolytic potential of marine hydrobionts. At first, tissue extract was separated bу gel filtration chromatography. Further zymography of obtained fractions revealed the presence of active enzymes which further were identified as collagenolytic.